Pengaruh Program Cashback Xtra dan Gratis Ongkir Xtra terhadap Peningkatan Penjualan Toko “Tencomp” pada E-Commerce Shopee - Murniwati Murniwati; Yusnaldi Yusnaldi; Fasa Azzahra (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
This study aims to determine the effect of the Cashback Xtra and Free Xtra Delivery programs on increasing sales. This study uses Quantitative methods with 100 respondents with the criteria of